Nursing problems in patients with pulmonary tuberculosis and nurses’ role solving such problems - Gerikienė, Vitalija; Metrikytė, Indrė (Slauga. Mokslas ir praktika, 2020)
The aim of the study: to analyze nursing problems in patients with pulmonary tuberculosis and role of nurses in their decision. Material and methods. A qualitative study was conducted on semi-structured interview with 7 general practice nurses caring for tuberculosis-treated patients for at least 10 years. The interview questionnaire consisted of 16 open-ended questions. Using the method of qualitative content analysis, the data obtained during the interviews are divided into categories and subcategories, justifying the statements made by the participants of the study. Conclusions. Nurses participating in the study indicated that the patients were faced with these physical nursing problems (malnutrition, physical exhaustion, non-adherence of treatment regime, etc.), social problems (unemployment, limited communication skills, etc.) and psychological problems (fear, despair, anger). General practice nurses participating in the study are teaching patients about disease prevention and eating habits, carry doctor‘s appointments, by solving social problems help to prepare documents, promote treatment. Psychological support is not provided sufficiently for the patients.